2015
DOI: 10.1371/journal.pone.0121809
|View full text |Cite
|
Sign up to set email alerts
|

The Pitch Imagery Arrow Task: Effects of Musical Training, Vividness, and Mental Control

Abstract: Musical imagery is a relatively unexplored area, partly because of deficiencies in existing experimental paradigms, which are often difficult, unreliable, or do not provide objective measures of performance. Here we describe a novel protocol, the Pitch Imagery Arrow Task (PIAT), which induces and trains pitch imagery in both musicians and non-musicians. Given a tonal context and an initial pitch sequence, arrows are displayed to elicit a scale-step sequence of imagined pitches, and participants indicate whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 29 publications
7
55
0
Order By: Relevance
“…This study yields a rich view of reported mental control in everyday musical imagery, but we should note that it relies on self-reported experiences. Nevertheless, despite happening in the field and using self-reports, our findings fit with lab-based auditory imagery work using behavioral measures: people are relatively good at controlling their inner musical experiences when instructed (Foster et al, 2013;Gelding et al, 2015). Additionally, past experiencesampling work shows that self-reports are more accurate when they are collected close to when an experience happens (Schwarz, 2012).…”
Section: Discussionsupporting
confidence: 71%
“…This study yields a rich view of reported mental control in everyday musical imagery, but we should note that it relies on self-reported experiences. Nevertheless, despite happening in the field and using self-reports, our findings fit with lab-based auditory imagery work using behavioral measures: people are relatively good at controlling their inner musical experiences when instructed (Foster et al, 2013;Gelding et al, 2015). Additionally, past experiencesampling work shows that self-reports are more accurate when they are collected close to when an experience happens (Schwarz, 2012).…”
Section: Discussionsupporting
confidence: 71%
“…However, in addition to our correlational findings and previous behavioral and neuroimaging findings, more research is needed to confirm these results, preferably measuring imagery ability in experimental settings (cf. Gelding et al, 2015). If the relations reported here are confirmed and their mechanisms are identified, this would have implications for transfer effects between modalities and relevant health interventions.…”
Section: The Relation Between Imagery Stimulus Modalities and Intentimentioning
confidence: 56%
“…These findings suggest that individuals who are experienced with music score higher in imagery aspects specifically for music (the activity which they have gained experience in), rather than in imagery aspects in the general imagery modality (auditory) or a different one (e.g., visual). A potential explanation offered by Gelding, Thompson, & Johnson (2015) is that it is the use of strategy in musical imagery, rather than simply musical experience, that leads to better performance of musicians in musical imagery tasks.…”
Section: Individual Differences In Mental Imagery 26mentioning
confidence: 99%
“…The BAIS control (BAIS-C) subscale predicts performance on musical imagery related tasks (Gelding et al 2015) and sensorimotor synchronization both in terms of absolute synchrony with a beat and anticipatory timing (predicting, rather than reacting to, beat intervals; Colley et al 2018). The individual is asked to imagine a particular auditory experience (which might be musical, verbal, or comprised of miscellaneous environmental sounds) and either to self-rate how vivid they find the experience (vividness subscale) or how easy they find it to control the experience, perhaps by transforming the imagined sound into a related but different sound.…”
Section: Introductionmentioning
confidence: 99%